Selective Friedel–Crafts Acylation Reactions of 2-Arylphenoxyacetic Acids: A Simple and Efficient Methodology to Synthesize Dibenzoxepine and Arylcoumaranone Derivatives - Wang, Jialin; Liu, Jiaqi; Lan, Hao; Chu, Wenyi; Sun, Zhizhong (Synthesis, 2015)
Intramolecular Friedel–Crafts acylation reactions of 2-arylphenoxyacetic acids are accomplished using trifluoroacetic anhydride or trifluoromethanesulfonic acid at 0 °C or room temperature. Depending on the reaction conditions, dibenzoxepines or arylcoumaranones are obtained in good yields and with high selectivities (83–100%). Plausible mechanistic pathways for the selective formation of the different reaction products are discussed.
Keywords: Friedel–Crafts acylations; 2-arylphenoxyacetic acids; dibenzoxepines; arylcoumaranones; regioselectivity